Tinjauan Kebutuhan Rak Penyimpanan Rekam Medis di Rumah Sakit Annisa Bogor Tahun 2022 - Annisa Nur Salsabila; Wiwik Viatiningsih; Lily Widjaja; Laela Indawati (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Hospital is a health service institution by providing outpatient and inpatient services. Each hospital also has an obligation to have a Medical Record Unit. Medical records are files that contain records or documents such as patient identities, results of diagnoses, actions, and treatments as well as services that have been provided to patients. In the context of administering medical records, health service facilities are required to provide the necessary facilities. One of them is a medical record storage rack to store medical records. Based on the results of research at the Medical Record Unit of the Annisa Hospital, Bogor, it was found that the medical record storage rack was inadequate and some medical records were piled on the floor, making it difficult for officers to find medical records when needed and services at the polyclinic became hampered. The purpose of this study was to determine the need for medical record storage racks for the next 5 years at Annisa Hospital Bogor in 2022. The study was conducted using a quantitative descriptive method, using a non-random sampling method with saturated sampling technique. From the results of the study, the Annisa Bogor Hospital still lacks medical record storage rack facilities which currently have 12 wooden shelves and 3 Roll O'packs, an additional rack of 9 Roll O'packs is needed. The storage area at Annisa Hospital Bogor is sufficient because the area needed for the next 5 years is 61.3 m2. Meanwhile, the current room area is 120 m2 combined with the medical record officer's workspace.